Implementasi Sistem Manajemen Halal sebagai Investasi Spriritual dalam Perspektif Pelaku Bisnis - Audia Zein; Novien Rialdy (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
The Halal Management Sistem (HMS) has often been positioned as an administrative compliance tool that focuses on regulatory and certification requirements. This approach has the potential to simplify the meaning of halal by overlooking the inherent values, especially in the context of Muslim businesses. This study aims to interpret the understanding of the Halal Management Sistem not only as an administrative compliance mechanism, but also as an expression of worship and spiritual commitment in business practices. This study uses a qualitative approach through a literature review of scientific articles, books, and relevant publications discussing halal management, Islamic business ethics, and the perspectives of business actors. The results of the study show that the HMS is understood by business actors as a manifestation of religious obedience integrated into economic activities, where the application of halal principles is seen as part of devotion to God and a form of moral responsibility in running a business. In this understanding, administrative compliance is positioned as an implication of spiritual awareness, not as the main objective of the sistem's implementation. The research findings also indicate that the spiritual meaning of SMH encourages consistency in halal practices and strengthens long-term business orientation. Conceptually, this study has implications for the development of halal management studies by placing the spiritual dimension as the main foundation in the implementation of the Halal Management Sistem, particularly in supporting sustainable and ethical business practices.